Influence of Perfluorooctanoic Acid on the Transport and Deposition Behaviors of Bacteria in Quartz Sand - D. Wu; Tong, M.; Kim, H. (Environmental Science and Technology, 2016)
The significance of perfluorooctanoic acid (PFOA) on the transport and deposition behaviors of bacteria (Gram-negative Escherichia coli and Gram-positive Bacillus subtilis) in quartz sand is examined in both NaCl and CaCl2 solutions at pH 5.6 by comparing both breakthrough curves and retained profiles with PFOA in solutions versus those without PFOA. All test conditions are found to be highly unfavorable for cell deposition regardless of the presence of PFOA; however, 7%-46% cell deposition is observed depending on the conditions. The cell deposition may be attributed to micro- or nanoscale roughness and/or to chemical heterogeneity of the sand surface. The results show that, under all examined conditions, PFOA in suspensions increases cell transport and decreases cell deposition in porous media regardless of cell type, presence or absence of extracellular polymeric substances, ionic strength, and ion valence. We find that the additional repulsion between bacteria and quartz sand caused by both acid-base interaction and steric repulsion as well as the competition for deposition sites on quartz sand surfaces by PFOA are responsible for the enhanced transport and decreased deposition of bacteria with PFOA in solutions. © 2016 American Chemical Society.
Keywords: acid; Acid base interaction; article; Bacillus subtilis; Bacteria; bacterial cell; Bacteriology; bacterium; Break through curve; cell transport; cells; cells by body anatomy; Chemical heterogeneities; Cytology; Deposition; Deposition behavior; Enhanced transports; Escherichia coli; Extra-cellular polymeric substances; Gram positive bacterium; heterogeneity; Ionic strength; Nano-scale roughness; Negibacteria; nonhuman; Perfluorooctanoic acid; pH; polymer; Porous materials; Posibacteria; Quartz; roughness; Sand; silicon dioxide; solution; transport process